Ce que « sociologiser le biologique » peut bien vouloir dire - Chloé Mondémé (Tracés)
Bernard Lahire’s last book aims at “sociologising biology” by examining the ethological factors explaining and conditioning human sociality and society. As such, it instead looks like a classical reductionist program to biologise social behaviour (albeit free from genetic determinism) as defended by sociobiology fifty years ago. The overall argument rests on diverse references from this framework and the naive belief in the unity of biology (as a discipline somehow immune to internal debates and controversies). Recent anthropological programs grounded in evolutionary perspectives that could have provided interesting and informed discussions are neglected.